2001
DOI: 10.1128/iai.69.11.6881-6886.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deficiency of Tumor Necrosis Factor Alpha or Both of Its Receptors onStreptococcus pneumoniaeCentral Nervous System Infection and Peritonitis

Abstract: Tumor necrosis factor alpha (TNF-␣) and TNF-␤ are key mediators in bacterial inflammation. We therefore examined the role of TNF-␣ and its two receptors in murine pneumococcal central nervous system infection. TNF-␣ knockout mice and age-and sex-matched controls and TNF receptor (p55 and p75)-deficient mice and heterozygous littermates were infected intracerebrally with a Streptococcus pneumoniae type 3 strain. Mice were monitored until death or were killed 36 h after infection. Bacterial titers in blood, sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 43 publications
0
59
0
3
Order By: Relevance
“…Furthermore, anti-TNF␣-treated mice died of pneumococcal pneumonia significantly sooner than control mice. Moreover, in a murine model of pneumococcal peritonitis, 100 colony-forming units of S pneumoniae produced fatal peritonitis in TNF␣-deficient mice, but not in wild-type mice (32). TNF deficiency also led to a substantial increase in the level of pneumococci in blood and the spleen.…”
Section: Tnf␣ Inhibition and Sepsismentioning
confidence: 99%
“…Furthermore, anti-TNF␣-treated mice died of pneumococcal pneumonia significantly sooner than control mice. Moreover, in a murine model of pneumococcal peritonitis, 100 colony-forming units of S pneumoniae produced fatal peritonitis in TNF␣-deficient mice, but not in wild-type mice (32). TNF deficiency also led to a substantial increase in the level of pneumococci in blood and the spleen.…”
Section: Tnf␣ Inhibition and Sepsismentioning
confidence: 99%
“…In this regard it will be interesting to define whether MBL interacts with TLRs that play a key role in NF-B-dependent secretion of TNF-␣. It is clear from clinical studies with TNF-␣ antagonists and in TNF null mice that TNF-␣ plays a key role in host defense, thus the sluggish TNF-␣ response in MBL null mice is likely to contribute toward the susceptibility of these mice to infection (24,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that proinflammatory cytokines, such as IL-1, tumor necrosis factor alpha (TNF-␣), IL-6, and IL-18, play protective roles against pneumococcal infection (22,26,48,54,55). Moreover, gamma interferon has been demonstrated to protect mice against infection with S. pneumoniae by promoting the accumulation of neutrophils in the infected lung (34).…”
mentioning
confidence: 99%